Reflexión acerca de la formación de ingenieros y la educación energética - Zapata Peña, Jair; Castro M., Jhonn E.; Agudelo, Alexander (Revista Científica, 2011)
In this work one presents the development of a project of research, which seeks to establish factors that affect in the processes of education on the concept of energy that they would favor the engineers education in the frame of the sustainability. For this intention one works with teachers of the university Institution the liberators with whom it is investigated by the way in how they teach and spread the concepts of energy and his relation with the sustainability in the context of the energetic education.